Cocoa Pods with Different Nitrogen Sources Fermented by Using Pleurotus ostreatus as Poultry Feed - Nuraini , Nuraini; Nur, Yuliati Shafan; Djulardi, Ade (International Journal of Poultry Science, 2019)
Background and Objective: Cocoa pods can be used as a nonconventional animal feed but their utilization is limited due to their high crude fiber (lignin and cellulose) and low crude protein content. Fermentation with Pleurotus ostreatus, a lignocellulolytic fungus (producing ligninase and cellulase enzymes), has been used to increase crude protein (CP) levels and quality. This study evaluated the nutrient content and quality of cocoa pods fermented in combination with different nitrogen sources, such as tofu waste (TW), soy meal waste (SMW) and rice bran (RB), using Pleurotus ostreatus. Materials and Methods: The experiment was performed by using a completely randomized design with 4 treatments, namely, A (100% CP), B (80% CP+20% TW), C (80% CP+20% SMW) and D (80% CP+20% RB) and 5 replicates. Subsequently, crude protein, crude fiber (CF), nitrogen retention, crude fiber digestion and cellulose enzyme activity were measured. Results: The results of the experiment showed that cocoa pods with the tofu waste nitrogen source fermented with Pleurotus ostreatus significantly reduced CF and increased crude protein content, nitrogen retention, crude fiber digestion and cellulase activity (p<0.01). Conclusion: An 80% CP with 20% TW combination fermented with Pleurotus ostreatus was identified as the best condition for improving the nutrient content and quality of cocoa pods.